2019
DOI: 10.1051/0004-6361/201732423
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of imaging the event horizon of Sagittarius A* from space

Abstract: Context. It has been proposed that Very Long Baseline Interferometry (VLBI) at sub-millimeter waves will allow us to image the shadow of the black hole in the center of our Milky Way, Sagittarius A* (Sgr A*), and thereby test basic predictions of the theory of general relativity. Aims. This paper presents imaging simulations of a new Space VLBI (SVLBI) mission concept. An initial design study of the concept has been presented in the form of the Event Horizon Imager (EHI). The EHI may be suitable for imaging Sg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 117 publications
2
98
0
1
Order By: Relevance
“…A logarithmic transfer function, with the color range spanning three orders of magnitude in dynamic range, is used to highlight weak features in the jet. vertical offset, as in the Event Horizon Imager (EHI) concept (Roelofs et al, 2018) could easily be accommodated in a space-ground architecture by the simple addition of a second satellite in MEO. The reverse statement is not true; it would be extremely difficult, if not impossible, to incorporate a number of additional satellites (and ground stations) into the EHI architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A logarithmic transfer function, with the color range spanning three orders of magnitude in dynamic range, is used to highlight weak features in the jet. vertical offset, as in the Event Horizon Imager (EHI) concept (Roelofs et al, 2018) could easily be accommodated in a space-ground architecture by the simple addition of a second satellite in MEO. The reverse statement is not true; it would be extremely difficult, if not impossible, to incorporate a number of additional satellites (and ground stations) into the EHI architecture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Palumbo (2018) explored an array consisting of four telescopes in LEO, optimized for dynamical imaging. Roelofs et al (2018) explored a minimal configuration of two MEO satellites in a configuration such that the orbits slowly evolve over the course of six months to image Sgr A*. The uniting theme in these studies is that they have focused on a single scientific case and identified a single type of array to address that specific case.…”
Section: General Approachmentioning
confidence: 99%
“…That said, the presence of the H-maser on board the RadioAstron spacecraft made it possible to conduct the ad hoc Gravitational Redshift Experiment (Litvinov et al, 2018;Nunes et al, 2019). Future advanced SVLBI systems operating at millimetre and sub-millimetre wavelengths (Andrianov et al, 2019;Fish et al, 2019;Kudrishov et al, 2019;Linz et al, 2019;Roelofs et al, 2019) might require new approaches to space-borne telescope heterodyning.…”
Section: Local Vlbi Heterodynesmentioning
confidence: 99%
“…A more realistic simulation is given by [11], which calculated the image of a Schwarzschild black hole with the standard thin accretion disk. [12][13][14] simulated the image for the Kerr black hole and other accretion disk models. In order to compare observations with theories, the EHT collaboration [5,6,15] simulated the accretion matters based on the general relativistic magnetohydrodynamic (GRMHD, see [16] for pedagogical resources) simulations and produced the images by ray tracing [17].…”
Section: Introductionmentioning
confidence: 99%